Oviposition selection in spotted lanternfly: impact of habitat and substrate on egg mass size and hatchability - Liu, Houping (Frontiers in Insect Science, 2022)
Oviposition strategies adopted by insects (e.g., habitat selection, substrate preference, egg size, clutch size, structure, arrangement, parental care, etc.) are critical to the survival and development of their eggs. The impact of habitat and oviposition substrate on spotted lanternfly egg mass size and hatchability was studied in Pennsylvania through laboratory observations and field monitoring in 2019 and 2021. Eggs were arranged in single layers of 1–13 columns (1–18 eggs/column) on surfaces of various types of oviposition substrates, with the longest column(s) in the middle of the egg mass. Egg mass size was positively correlated with column number, with a mean of 26.6–35.1 (0–105) eggs/egg mass for different samples. Significant differences in egg mass size were observed between study sites, with larger egg masses found at Wertz (44.8), Sam Lewis (40.6), Pinnacle (39.1), Marsh Creek (37.9), Susquehannock (34.5), and Memorial Lake (33.3); and smaller egg masses at Nolde Forest (25.0), Gordon (24.4), and Antietam (21.0). Significant differences were also detected between types of oviposition substrates with smaller egg masses found on American hornbeam (22.7). In general, more (31.6–48.0%) eggs hatched in the field compared with the laboratory (10.0%). Egg hatch success was positively correlated with egg mass size, with the highest rates recorded on American beech, American hophornbeam, black birch, black cherry, black locust, hackberry, Norway maple, red maple, and sweet cherry at Wertz, Marsh Creek, Memorial Lake, and Pinnacle. Potential (positive or negative) impacts of tree-of-heaven density, initial infestation, treatment history, and incubation conditions are discussed.